Synergistic Effect of Essential Oils and Rhamnolipid on Xanthomonas citri Subsp. citri - Sereia, Maria Olimpia Pereira [UNESP]; dos Santos, Eduarda Araujo [UNESP]; Leite, Lucas Prado [UNESP]; Neves, Raphael Culim [UNESP]; Marin, Vítor Rodrigues [UNESP]; Ferreira, Henrique [UNESP]; Contiero, Jonas [UNESP]; Sass, Daiane Cristina [UNESP] (MDPI, 2025)
Citrus canker, caused by Xanthomonas citri subsp. citri, is a devastating disease that affects citrus production and trade worldwide. Traditional control methods, based on copper compounds, are effective but pose environmental and health risks due to their toxicity and potential for bioaccumulation. This study evaluates the synergistic potential of essential oils (EOs) and rhamnolipids as sustainable alternatives for disease management. Four EOS (citronella, palmarosa, geranium, and clove) were tested for their antibacterial activity. Citronella EO showed a 90% inhibitory concentration (IC 90) of 0.15% (v/v) and a minimum bactericidal concentration of 0.25% (v/v), while the other EOs showed IC 90 and bactericidal activity at 0.06% (v/v). Rhamnolipids (RHLs), biosurfactants produced by Pseudomonas aeruginosa, inhibited X. citri at a concentration of 0.3% (v/v). The combination of citronella EO and RHLs showed a synergistic effect, reducing the inhibitory concentration of citronella by 50% and that of RHLs by more than 90%. In addition, the combined formulation permeabilized more than 80% of bacterial membranes and reduced biofilm formation. In contrast, other oils tested in combination with rhamnolipid showed independent effects. These results indicate that EOs and rhamnolipids represent an environmentally safe strategy for the control of X. citri subsp. citri that overcomes the limitations of conventional methods while reducing environmental and health impacts.